Diversidade genética de isolados do complexo Diaporthe/Phomopsis em soja no Brasil - Soldera, Maria Cecília do Amaral (2010)
The Diaporthe/Phomopsis complex is responsible for diseases known as the pod and stem blight, stem canker and seed decay. The aim of this work were to identify and determine the genetic diversity of isolates from different regions, using morphological and molecular techniques. One hundred and thirty-five isolates were characterized morphologically and differentiated into seven groups. Were used 10 primers in the RAPD technique and polymorphism obtained was made a dendrogram showing large genetic diversity among isolates, with similarity coefficients ranging from 0.45 to 1.0. PCR-RFLP analysis were performed using restriction enzymes Alu I, Rsa I and Hha I for ITS region, ß-tubulin gene, Rsa I and HhaI for the elongation factor EF-1α gene. The comparison of digested fragments showed great polymorphism among the isolates. Phylogenetic analysis for each gene studied allowed to identify and infer the evolutionary relationships of the isolates. These results indicated high genetic diversity and the phylogenetic relationships of isolates Diaporthe/Phomopsis complex from different geographical regions of the country.